2017
DOI: 10.1130/g38s394.1
|View full text |Cite
|
Sign up to set email alerts
|

Fault-controlled dolomitization in a rift basin

Abstract: There are numerous examples of fault-controlled, so-called hydrothermal dolomite (HTD), many of which host economic mineral deposits or hydrocarbons, but there remains a lack of consensus as to how they form. In particular, multiple phases of diagenetic overprinting can obscure geochemical fingerprints. Study of a Cenozoic succession with a relatively simple burial history here provides new insights into the development of differentially dolomitized beds. The Hammam Faraun fault (HFF) block within the Suez Rif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 11 publications
3
79
0
Order By: Relevance
“…On the Hammam Faraun Fault (HFF) block, Gulf of Suez, non-stratabound dolomitization is observed in proximity to the HFF, with numerous, discontinuous stratabound dolostone bodies extending into the footwall for up to 2 km. Hollis et al (2017) demonstrated that in this wellexposed example, the stratabound dolostone pre-dates, and is not genetically related to, cross-cutting non-stratabound dolostone. This is contrary to the interpretation of many dolostone bodies formed in proximity to faults.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…On the Hammam Faraun Fault (HFF) block, Gulf of Suez, non-stratabound dolomitization is observed in proximity to the HFF, with numerous, discontinuous stratabound dolostone bodies extending into the footwall for up to 2 km. Hollis et al (2017) demonstrated that in this wellexposed example, the stratabound dolostone pre-dates, and is not genetically related to, cross-cutting non-stratabound dolostone. This is contrary to the interpretation of many dolostone bodies formed in proximity to faults.…”
Section: Introductionmentioning
confidence: 66%
“…2 Massive dolostone bodies, up to 500 m wide (distance from the HFF) and 60 to 80 m thick. Dolostone tongues associated with these massive bodies extend for up to 100 m away from the massive dolostone bodies, forming 1 to 5 m thick bands (Hirani, 2014;Hollis et al, 2017). This paper focuses on the stratabound dolostone bodies and the major controls associated with their formation.…”
Section: Field Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 km of maximum displacement (Suez Rift, Egypt; Figure ). Dolomitization occurs in the form of discrete, non fabric selective bodies that cross‐cut stratigraphy and older, stratabound dolostone bodies (Hirani et al., ; Hollis et al., ). The outcrop provides an opportunity to understand the controls on the localization of dolomitization within a relatively young (Tertiary) extensional basin that has not undergone subsequent tectonic rejuvenation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other mechanisms could have produced a weak thermal gradient, such as a little geothermal anomaly related to the transtensional tectonic setting that was active in Gargano Promontory at the time of dolomitization. In such a tectonic setting, dolomitization models that rely on geothermal convection of former seawater circulating along faults (Corbella et al, 2014;Hollis et al, 2017) can explain the dolomitization in Gargano Promontory; especially the fault-plane convection model proposed by Hollis et al (2017). This model relies on seawater that descends down discrete, surface-breaching faults (Fig.…”
Section: Model Of Fault-controlled Dolomitizationmentioning
confidence: 99%